As ruínas do patrimônio na Cidade de Goiás : residências deterioradas testemunham uma nova imagem do patrimônio – 1950/2021 - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
This work aims to reconsider the ruins existing in the Historic Center of the City of Goiás, State of Goiás, Brazil (Centro Histórico da Cidade de Goiás-GO, Brasil). Ruin is understood to be a physical condition characterized by the degradation of the building, with loss of its previous characteristics, and not only the temporal factor being the only element that causes the ruination. For the study and analysis of the ruins, some cases were selected in the Historic Center of the City of Goiás for a better understanding of the disintegration of the body of the heritage, analyzing how this alters the Vilaboense landscape. In the study, it is understood that not only the ruined houses are elements that testify to the survival of what already existed, but they also contemplate the causes of destruction and what can be forgotten. In this way, it is possible to differentiate preservation and “Tombamento” (legal protection of the cultural heritage preservation), emphasizing that only the current legislation is inefficient for the process of preserving a place, a property and its memory. It is also reflected that preservation, as a social project, obeys power struggles, choices and exclusions, and it discusses the limits and possibilities of heritage and its fractures based on the new landscape that is being built over time. The study also deals with the danger of Vilaboense heritage becoming a consumer product, "fetishized", manufactured to serve a market that does not care about the sensibilities, stories and emotions present, making the Historic Center a setting for shows that do not represent the City as a whole, therefore, delimiting places and excluding people. The final product of this research is an E-book (digital book), which presents the work in a summarized and didactic way, with photographs and problematizations regarding the presence of the ruins in the Historic Center.
The ruins of heritage in the Cidade de Goiás : damaged residences witness a new image of heritage – 1950/2021
Keywords: Patrimônio cultural; Ruínas; Cidade de Goiás; Memória; Cultural heritage; Ruins; City of Goiás (Cidade de Goiás); Memory; CIENCIAS HUMANAS::HISTORIA